Role of Radiopharmaceuticals in Diagnosis and Therapy - Rajurkar, N.S. (Asian Journal of Chemistry, 2012)
The lecture begins with the glimpses of development of the subject of radiochemistry. This is followed by synthesis of radioisotopes and the various units used for measurement of radiations. The major uses of radioisotopes in medical field include diagnosis, therapy and sterilization. A radiopharmaceutical is a radioactive compound used for the diagnosis and therapeutic treatment of various human diseases. Radiopharmaceutical products include inorganic compounds, organic compounds, peptides, proteins and monoclonal antibodies, which are labeled with radionuclides with half-lives varying from a few minutes to several days. The use of radiopharmaceutical gives both anatomical and physiological information of the organ. Its designing is based on the preferential localization of radiopharmaceutical in a given organ or participation of it in the physiologic function of the organ. The general principles for use of radiopharmaceuticals and their properties for ideal diagnostic and therapeutic purposes are discussed in brief. The principle of radionuclide generator with an example of technetium generator is described. The applications of radiopharmaceuticals in diagnosis of various diseases using Positron emission tomography, static and dynamic imaging are discussed. Radiation therapy is a technique, which is widely used for the treatment of cancer by delivering radiation dose to the affected lesion with the help of tiny sealed radioactive sources. In teletherapy the source is kept away from the lesion and radiation beam is directed to the affected part with the help of collimators while in brachytherapy the tiny radiation sources are deployed for the treatment of cancer and benign diseases by placing them in the close proximity of affected lesion. Preparation of I-125 brachytherapy source for the treatment of retinoblastoma is discussed in brief at the end of lecture.